Teaching Evaluation: Waiting for Initiatives - Alejandro Canales Sánchez (Universidad Autónoma de Baja California, 2008)
In this text, it is sustained that, despite the fact that the teaching activity is one of the main functions of higher education institutions or even the only one in most of them, it hasn't been reflected in the leading initiatives that have been set in motion in this area for the last two decades. In particular, it points out that the wide evaluation politics established in the education system during the late eighties, didn't consider the teaching activity as a concern issue for the mechanisms or rewards in the evaluation system. Even though the implementation of new actions tried to repair the situation, mainly by improving the quality of working time and the qualifications of the personnel performing these activities; teaching, in strict sense, and the design or application of a new evaluation scheme to strengthen it, didn't get better.